PENGARUH STRUKTUR KEPEMILIKAN SAHAM, KUALITAS AUDITOR EKSTERNAL, STRUKTUR KEUANGAN PERUSAHAAN TERHADAP MANAJEMEN LABA (INCOME DECREASING) - Sarah Devina; Paulina Sutrisno (Tirtayasa Ekonomika, 2016)
The research aims is to examine the influence of ownership structure (managerial ownership, ownership concentration and institutional ownership), firm size, audit quality, financial structure and independent board on negative discretionary accruals as a proxy for earnings management income decreasing by empirical analyze. Population of this research are all non-financial listed companies in Indonesia Stock Exchange from 2011 to 2014. The sample is collected using the purposive-sampling method, then 181 companies meet the criteria for sample. This research uses multiple linear regression method for data analysis. The result of this research shows ownership concentration, institutional ownership, firm size and audit quality had influence on earnings management practice (income decreasing). Other independent variables such as managerial ownership, financial structure and independent board had no influence on earnings management practice (income decreasing). Keywords: ownership structure, audit quality, financial structure, and earnings management